Efficacy of probiotic and green tea mouthrinse on salivary pH - Shashibhushan Kukkalli Kamalaksharappa; Ramya Rai; Prashant Babaji; M C Pradeep (Wolters Kluwer Medknow Publications, 2018)
Objectives: The aim of the study was to assess the efficacy of probiotic and green tea mouthrinse on salivary pH. Method: Study was conducted over a period of one month among 40 healthy school children aged between 6-8 years. The subjects who fulfilled inclusion criteria were selected and randomly divided into 2 groups namely probiotic and green tea groups. Salivary pH was recorded at baseline (0 day) and at the end of the specified time period using GC pH strips. Statistical analysis was done using paired 't' test P < 0.05 was considered statistically significant. Result: The comparison of mean pH scores for green tea showed that the pH of saliva was increased in the children after rinsing with green tea (6.15 to 7.65) and was statistically significant (p<0.001). Similarly when pre and post mean pH was compared in the probiotic group pH increased from (6.45 to 6.65) however, the results were not statistically significant. Conclusion: The study conducted shows the beneficial effects of green tea in providing a alkaline environment which is conducive to the oral health of children.